Protecting farmers' data privacy and confidentiality: Recommendations and considerations - Kaur, Jasmin; Hazrati Fard, Seyed Mehdi; Amiri-Zarandi, Mohammad; Dara, Rozita (Frontiers in Sustainable Food Systems, 2022)
With the increasing use of precision agriculture and technological development, the agricultural sector has been majorly transformed. Precision agriculture uses technological innovations such as sensors, drones and data analysis tools to improve the productivity of resources and management decisions on the farm. Since these technologies collect a large amount of data related to the farm, the farmers are concerned about the privacy of their data. The farmers are worried about unauthorized access, collection and sharing of their data with third parties by the agricultural technology providers (ATPs). Furthermore, the ambiguity of agreements and legal frameworks around data collection, processing, and sharing may result in uncertainty in data privacy practices. Furthermore, this situation is aggravated with a lack of adoption of best practices and standards for farm data protection. Violation of privacy can cause farmers’ reluctance to adopt new technologies which can affect all stakeholders that use the farming system. Protecting farmers’ privacy and respecting their rights on the collected data should be addressed collectively by the actors in the farming ecosystem, including farmers, agricultural technology providers, governments, and supply chain stakeholders. This paper aims at providing recommendations on how to minimize privacy risks and concerns for farmers and reviews some of the best practices.